2011
DOI: 10.3402/polar.v30i0.7210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laptev Sea flaw polynyas on the atmospheric boundary layer and ice production using idealized mesoscale simulations

Abstract: The interaction between polynyas and the atmospheric boundary layer is examined in the Laptev Sea using the regional, non-hydrostatic Consortium for Small-scale Modelling (COSMO) atmosphere model. A thermodynamic sea-ice model is used to consider the response of sea-ice surface temperature to idealized atmospheric forcing. The idealized regimes represent atmospheric conditions that are typical for the Laptev Sea region. Cold wintertime conditions are investigated with sea-ice–ocean temperature differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 29 publications
0
37
0
2
Order By: Relevance
“…Effects of Arctic leads and polynyas on the atmospheric boundary layer (ABL) have been addressed in numerous experiments applying numerical weather prediction (NWP) models, large-eddy simulation models, and process models for ABL dynamics (e.g., Ledley 1988;Vihma 1995;Esau 2007;Lüpkes et al 2008aLüpkes et al , b, 2012Ebner et al 2011). These studies have yielded a better understanding of various processes: the magnitude of turbulent fluxes of sensible and latent heat, the effects on air temperature and humidity, formation of sea smoke, the rise of a heat plume under variable background stratification, and the recapture of part of the heat by sea ice downwind of the lead/polynya, as well as on the effect of thin ice on the lead/polynya surface.…”
Section: Model Experiments Addressing Processes and Recent Climatementioning
confidence: 99%
“…Effects of Arctic leads and polynyas on the atmospheric boundary layer (ABL) have been addressed in numerous experiments applying numerical weather prediction (NWP) models, large-eddy simulation models, and process models for ABL dynamics (e.g., Ledley 1988;Vihma 1995;Esau 2007;Lüpkes et al 2008aLüpkes et al , b, 2012Ebner et al 2011). These studies have yielded a better understanding of various processes: the magnitude of turbulent fluxes of sensible and latent heat, the effects on air temperature and humidity, formation of sea smoke, the rise of a heat plume under variable background stratification, and the recapture of part of the heat by sea ice downwind of the lead/polynya, as well as on the effect of thin ice on the lead/polynya surface.…”
Section: Model Experiments Addressing Processes and Recent Climatementioning
confidence: 99%
“…On the basis of airborne observations and high-resolution modelling, Lüpkes et al (2008bLüpkes et al ( , 2012b concluded that convection over 1-2 km wide leads reached altitudes of 50-300 m depending on the boundary layer structure on the upstream side of leads. On the basis of aircraft in situ, drop sonde, and lidar observations, Lampert et al (2012) observed that over areas with many leads, the potential temperature decreased with height in the lowermost 50 m and then was nearly constant due to convective mixing up to the height of 100-200 m. When the leads were frozen and their fraction was small, however, an SBL extended up to a height of 200-300 m. Ebner et al (2011) showed in a modelling study that convective plumes generated over the Laptev Sea polynya influence atmospheric turbulence even 500 km downstream of the polynya, and Hebbinghaus et al (2006) found that cyclonic vortices can be generated or intensified over polynyas due to convective processes. Such processes over large polynyas may be important with respect to the drastic changes in sea ice cover observed in recent years.…”
Section: Atmosmentioning
confidence: 99%
“…Marcq and Weiss, 2012) and on coupled atmosphere-sea-ice-ocean modelling (e.g. Ebner et al, 2011). Challenges remain in the high sensitivity of winter air temperatures to sea ice concentration (Lüpkes et al, 2008a;Tetzlaff et al, 2013) in the representation of new, thin ice in atmospheric models (Tisler et al, 2008) and in the interaction of convective plumes with capping stable or near-neutral environments (Lüpkes et al, 2008b).…”
Section: Main Advances and Remaining Challenges In Individual Researcmentioning
confidence: 99%
“…It is also interesting to consider the impact of polynyas on local atmospheric temperatures (e.g., Raddatz et al, 2013;Ebner et al, 2011;Fiedler et al, 2010). Using ERA-Interim data, Onarheim et al (2014) found an air temperature increase of 7 K in the Whaler's Bay polynya between 1979 and 2012 associated with the observed decrease in sea ice cover.…”
Section: Polynya Impact On Atmospheric Temperaturesmentioning
confidence: 99%